Effects of Berberine and Its Derivatives on Cancer: A Systems Pharmacology Review - Zhang, Chaohe; Sheng, Jiyao; Li, Guangquan; Zhao, Lihong; Wang, Yicun; Yang, Wei; Yao, Xiaoxiao; Sun, Lihuan; Zhang, Zhuo; Cui, Ranji (Frontiers in Pharmacology, 2020)
Numerous studies have shown that berberine and its derivatives demonstrate important anti-tumor effects. However, the specific underlying mechanism remains unclear. Therefore, based on systems pharmacology, this review summarizes the information available on the anti-tumor effects and mechanism of berberine and its derivatives. The action and potential mechanism of action of berberine and its derivatives when used in the treatment of complex cancers are systematically examined at the molecular, cellular, and organismic levels. It is concluded that, with further in-depth investigations on their toxicity and efficacy, berberine and its derivatives have the potential for use as drugs in cancer therapy, offering improved clinical efficacy and safety.